How to Think Like a Computer Scientist C++ Version - Downey, Allen B.; Open Textbook Library (Open Textbook Library, 2012)
The goal of this book is to teach you to think like a computer scientist. I like the way computer scientists think because they combine some of the best features of Mathematics, Engineering, and Natural Science. Like mathematicians,computer scientists use formal languages to denote ideas (specifically computations). Like engineers, they design things, assembling components into systems and evaluating trade offs among alternatives. Like scientists, they observe the behavior of complex systems, form hypotheses, and test predictions.The single most important skill for a computer scientist is problem-solving. By that I mean the ability to formulate problems, think creatively about solutions, and express a solution clearly and accurately. As it turns out, the process of learning to program is an excellent opportunity to practice problem-solving skills. That's why this chapter is called "The way of the program."
Chapter 1: The way of the program -- Chapter 2: Variables and types -- Chapter 3: Function -- Chapter 4: Conditionals and recursion -- Chapter 5: Fruitful functions -- Chapter 6: Iteration -- Chapter 7: Strings and things -- Chapter 8: Structures -- Chapter 9: More structures -- Chapter 10: Vectors -- Chapter 11: Member functions -- Chapter 12: Vectors of Objects -- Chapter 13: Objects of Vectors -- Chapter 14: Classes and invariants -- Chapter 15: File Input/Output and apmatrixes
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks